Harnessing Flipbook-Based E-Modules to Foster Creativity in Science Education: A Systematic Review - Herawati, Wahyu Dwi; Nisa, Ana Fitrotun; Masjid, Akbar Al; Cahyani, Berliana Henu (Jurnal Pendidikan MIPA, 2024)
Digital-based learning is a transformation of education.  Teachers can now distribute lesson materials in a more effective and interesting manner thanks to a variety of tools and platforms. Among the most notable innovations in this area is is the use of e-modules, particularly flipbook-based e-modules. Students can immediately engage with the curriculum, explore, and develop their creativity in this more dynamic and interactive learning environment. The purpose of this study is to examine how flipbook-based IPAS e-modules can be used to enhance students' creativity. This research method employs SLR (Systematic Literature Review) following the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) guidelines, which involves analyzing several articles related to how the use of flipbook-based e-modules can enhance students' creativity, thereby achieving the expected learning outcomes, especially in the subject of IPAS. In order to find relevant publications for this literature review, the Publish or Perish (PoP) tool, which is indexed by Google Scholar, was used. Title, abstract, introduction, methods, results, discussions, and conclusions are the seven components of the PRISMA concept, which was used to assess the relevant articles after they were found using the requested keywords. The PoP program that is connected with Google Scholar has identified 25 out of 305 articles. The results of the study show that using e-modules based on flipbooks is able to increase students' creativity and produce the desired learning results. The use of flipbook-based e-modules certainly shows great potential in supporting more innovative and effective education.       Keywords: e-module, flipbook, student creativity, IPAS, teaching materials. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp2029-2051